2004
DOI: 10.1007/s00011-004-1249-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nicotine on basophil histamine release

Abstract: This study has demonstrated that nicotine agonists inhibit histamine release from human basophils. Further studies examining the effect of smoking on basophil activation are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…29 Smokers have higher rates of carriage of pneumococci 30 and higher rates of invasive pneumococcal disease. 5 Various substances in tobacco smoke (e.g., nicotine, nicotine-derived nitrosamine ketone) can influence dysfunction of numerous immune cell types, including macrophages, 6 basophils, 7 and mast cells. 8 For these reasons, respiratory infections were of particular interest, and did in fact show a slightly higher AOR of antibiotic usage (1.31) compared with infections overall (1.20) in the findings.…”
Section: Discussionmentioning
confidence: 99%
“…29 Smokers have higher rates of carriage of pneumococci 30 and higher rates of invasive pneumococcal disease. 5 Various substances in tobacco smoke (e.g., nicotine, nicotine-derived nitrosamine ketone) can influence dysfunction of numerous immune cell types, including macrophages, 6 basophils, 7 and mast cells. 8 For these reasons, respiratory infections were of particular interest, and did in fact show a slightly higher AOR of antibiotic usage (1.31) compared with infections overall (1.20) in the findings.…”
Section: Discussionmentioning
confidence: 99%
“…These receptors are believed to be inhibitory receptors as Thompson‐Cree et al . [7] have demonstrated a decrease in IgE‐mediated release of histamine by prior incubation of basophils with nicotine and a nicotine agonist, methyl‐2‐[3‐pyridyl] pyrolidine.…”
Section: Discussionmentioning
confidence: 99%
“…Muscarinic Acetylcholine (ACh) receptors have been characterised on human mast cells, the tissue‐based mediators of immediate hypersensitivity [4–6] and nicotinic ACh receptors are also suspected to exist on these cells and on basophils, their humoral counterparts [7]. As neuromuscular blocking drugs used in anaesthesia act on the nicotinic receptors on the neuro‐muscular junction, we considered the hypothesis that these drugs may also act on a nicotinic receptor on the cells involved in acute anaphylaxis; basophils and mast cells.…”
mentioning
confidence: 99%
“…Sudheer et al [45] reported that the nicotinic antagonist α 7 -bungarotoxin fluorescently bound to the surface of human basophils. Furthermore, in the presence of nicotine, treatment of anti-IgE-stimulated basophils dose-dependently decreased histamine degranulation in human basophils, suggesting that these cells may have functional nAChRs [14]. …”
Section: Introductionmentioning
confidence: 99%
“…Efferent neurons respond to proinflammatory mediators by releasing endogenous acetylcholine (ACh), which then binds to nicotinic ACh receptors (nAChRs) on various structural and immune cells [9,10,14,15,16]. This leads to the modulation of intracellular signaling cascades that control proinflammatory cellular responses [10,14]. nAChRs are a family of ligand-gated, pentameric ion channels, and 17 different subunits (α 1 -α 8 , α 9 , α 10 , β 1 -β 4 , δ, ϵ and γ) have been reported in humans [17,18,19].…”
Section: Introductionmentioning
confidence: 99%